2001
DOI: 10.2134/jeq2001.303878x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dissolved Organic Matter from Sludge and Sludge Compost on Soil Copper Sorption

Abstract: Interaction of Cu with dissolved organic matter (DOM) is an important physicochemical process affecting Cu mobility in soils. The aim of this study was to investigate the effects of DOM from anaerobically digested dewatered sludge and sludge compost on the sorption of Cu on an acidic sandy loam and a calcareous clay loam. In the presence of DOM, Cu sorption capacity decreased markedly for both soils, especially for the calcareous soil. The Cu sorption isotherms could be well described by the Freundlich equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
72
1
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(89 citation statements)
references
References 30 publications
11
72
1
5
Order By: Relevance
“…Dissolved organic carbon is the most mobile fraction of organic ligands that exist in soils and may assist in the transfer of metals through soil as organic complexes (Cao et al, 2003); greater concentrations of aromatic and phenolic compounds will produce soluble metal-organic complexes (Tapia et al, 2010;Vaca-Paulín et al, 2006). Copper mobility has been shown to increase with increasing DOC concentration and pH (Temminghof et al, 1997;Strobel et al, 2001), whilst Zhou and Wong (2001) reported that application of soluble organic carbon from sewage sludge reduced Cu sorption in soil due to development of soluble complexes, with the effect being greater at higher pH. There were no significant differences in pore water Zn and Mn concentrations compared to controls (Figs S4 and S5).…”
Section: Micronutrient Mobility and Dissolved Organic Carbonmentioning
confidence: 99%
“…Dissolved organic carbon is the most mobile fraction of organic ligands that exist in soils and may assist in the transfer of metals through soil as organic complexes (Cao et al, 2003); greater concentrations of aromatic and phenolic compounds will produce soluble metal-organic complexes (Tapia et al, 2010;Vaca-Paulín et al, 2006). Copper mobility has been shown to increase with increasing DOC concentration and pH (Temminghof et al, 1997;Strobel et al, 2001), whilst Zhou and Wong (2001) reported that application of soluble organic carbon from sewage sludge reduced Cu sorption in soil due to development of soluble complexes, with the effect being greater at higher pH. There were no significant differences in pore water Zn and Mn concentrations compared to controls (Figs S4 and S5).…”
Section: Micronutrient Mobility and Dissolved Organic Carbonmentioning
confidence: 99%
“…When CA causes the sludge to form crumbs and clay, i.e., changing the sludge structure, organic matter is increased accordingly. In regards to EDTA, the decrease of organic matter can be mainly attributed to leaching (Zhou and Wong, 2001). …”
Section: Organic Mattermentioning
confidence: 99%
“…It was reported that dissolved organic matter from cattle-manure slurry and sludge and sludge compost increases the solubility of cadmium, copper and zinc soil (Del Castilho et al 1993, Zhou andWong 2001). The results showed that soil available Pb was higher in SME treatments at T3 and T4.Therefore the positive effects of SME on Pb uptake by Helianthus annuus is the result of plant growth improvement and soil Pb solubilization.…”
Section: Translocation Factor and Pb Uptake By Plantmentioning
confidence: 93%